Being a vocational teacher in Sweden: Navigating the regime of competence for vocational teachers - Sofia Antera (International Journal for Research in Vocational Education and Training (IJRVET), 2022)
Context: Vocational teachers are called to constantly meet the upcoming needs in social and working life. In Sweden, the high demand for vocational teachers has led to their recruitment in the early stages of vocational teacher studies or even before teacher training. Entering this new community of practice, vocational teachers cross boundaries between their previous occupation and their teaching job, mediating the introduction of competence between them. In this context, the study explores vocational teachers' competence through their own perceptions, addressing important competence areas, as well as how competence is understood. Approach: The study employs a socio-cultural perspective on learning. Communities of practice establish their regime of competence, a set of principles and expectations that recognise membership. To be competent is translated as understanding the shared enterprise of the community, being capable and allowed to engage in it and, thus, interact with the other members and with the available resources. Hence, what is expected by members to know and to be is defined by the regime of competence and, hence, by the community. Comprised of 14 semi-structured interviews with vocational teachers in different vocational disciplines, employed both in upper secondary and adult education schools, the study adopts a qualitative research strategy. The research material was analysed thematically. Findings: According to findings, important competence comprise of up-to-date vocational competence supporting the performance of vocational teaching, but also interpersonal competence, including good communication and the construction of a close relationship with the students. The student-teacher relationship serves as the basis to match students with their work placement, facilitating higher work-based training quality. Moreover, maintaining a continuous development attitude and openness to critique are crucial for teachers. Finally, teachers approach competence focusing on its relationship to action and performance, while also referring to its situated nature. Therefore, to be competent is understood differently in different practices (teaching and occupational), highlighting the importance of understanding the uniqueness and duality within the regime of competence of vocational teaching. Conclusion: Teachers have described the importance of competence which was not developed during teacher training. Instead, important competences were often developed in the previous profession or informal teaching activities. Vocational teachers seem to value and utilise their previous occupational worker identities to a high extent. This should be considered when teacher training or in-service training is designed to support individuals in developing their (new) teacher identity.
Keywords: 330; Professional Competence Development; Vocational Teachers; Communities of Practice; Vocational Education and Training; VET in Sweden; Workplace Learning